2004
DOI: 10.1016/j.ejheart.2003.11.017
|View full text |Cite
|
Sign up to set email alerts
|

NT‐brain natriuretic peptide levels in pleural fluid distinguish between pleural transudates and exudates

Abstract: Background: Pleural effusion is not pathognomic and distinguishing between transudates and exudates often presents a diagnostic dilemma. The purpose of our study was to examine whether the inclusion of pleural fluid brain natriuretic peptide (BNP) measurement into the analysis improves the diagnostic accuracy of pleural effusion. Methods: The pleural effusion of 14 patients with CHF (group A) and 14 subjects with different pleural pathology (group B) were analyzed. Samples of pleural fluid and serum were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 7 publications
3
63
1
1
Order By: Relevance
“…4,7,10 Kolditz et al 4 demonstrated elevated levels of NT-proBNP in both serum and pleural fl uid of individuals with pleural effusions arising from cardiac disease and also described a high diagnostic accuracy of pleural fl uid NT-proBNP with an AUC of 0.98 (95% CI, 0.96-1.00). Additional investigations have confi rmed the accuracy of NT-proBNP in identifying CHF-related pleural effusions, with Han et al 11 reporting an AUC of 0.996 (95% CI, 0.990-1.003).…”
Section: Discussionmentioning
confidence: 99%
“…4,7,10 Kolditz et al 4 demonstrated elevated levels of NT-proBNP in both serum and pleural fl uid of individuals with pleural effusions arising from cardiac disease and also described a high diagnostic accuracy of pleural fl uid NT-proBNP with an AUC of 0.98 (95% CI, 0.96-1.00). Additional investigations have confi rmed the accuracy of NT-proBNP in identifying CHF-related pleural effusions, with Han et al 11 reporting an AUC of 0.996 (95% CI, 0.990-1.003).…”
Section: Discussionmentioning
confidence: 99%
“…Tomcsányi et al 15 showed that the criteria of Light et al 1 had a sensitivity of 93% and specificity of 43% for transudates. However, the pleural fluid NT-proBNP accurately differentiated between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in accordance with the recent studies that explored the diagnostic value of BNP and NT-proBNP in the etiology of pleural effusions. 2,[15][16][17][18][19][20] Han et al 2 measured pleural fluid and serum NT-proBNP levels in a consecutive series of 98 patients with heart failure and in 142 patients with other causes, and found that pleural fluid NT-proBNP levels among the heart-failure patients were significantly higher than others. Similarly, Porcel et al 18 retrospectively examined 117 patients with pleural effusion and found that the pleural fluid levels of NTproBNP were significantly higher in patients with cardiac transudates than in patients with effusion of other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Plevral efüzyonun nedenini belirlemek amacıyla plevral sıvı NT-proBNP ile yapılmış çalışmaların ayrıntı-lı sonuçları Tablo 1'de verilmiştir (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Bu tabloda Kolditz ve ark.…”
Section: Nt-probnp Ve Plevral Efüzyonunclassified